2012
DOI: 10.1186/bcr3172
|View full text |Cite
|
Sign up to set email alerts
|

Comparable frequency of BRCA1, BRCA2 and TP53 germline mutations in a multi-ethnic Asian cohort suggests TP53 screening should be offered together with BRCA1/2 screening to early-onset breast cancer patients

Abstract: IntroductionGermline TP53 mutations cause an increased risk to early-onset breast cancer in Li-Fraumeni syndrome (LFS) families and the majority of carriers identified through breast cancer cohorts have LFS or Li-Fraumeni-like (LFL) features. However, in Asia and in many low resource settings, it is challenging to obtain accurate family history and we, therefore, sought to determine whether the presence of early-onset breast cancer is an appropriate selection criteria for germline TP53 testing.MethodsA total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 22 publications
4
48
1
Order By: Relevance
“…The high incidence of leukaemia among the younger age group could be linked either to treatment (radiotherapy or chemotherapy) or to genetic mutations in the tumour suppressor genes CHEK2 and TP53 known as Li-Fraumeni syndrome, with the affected women being susceptible to develop multiple primary tumours early in life, such as breast cancer, acute adult leukaemia and soft tissue sarcomas. Several recent reports confirm this genetic linkage (Lynch et al 2008;Ruijs et al 2010;Lee et al 2012;Silva et al 2012).…”
Section: Patient-related Limitationsmentioning
confidence: 58%
See 1 more Smart Citation
“…The high incidence of leukaemia among the younger age group could be linked either to treatment (radiotherapy or chemotherapy) or to genetic mutations in the tumour suppressor genes CHEK2 and TP53 known as Li-Fraumeni syndrome, with the affected women being susceptible to develop multiple primary tumours early in life, such as breast cancer, acute adult leukaemia and soft tissue sarcomas. Several recent reports confirm this genetic linkage (Lynch et al 2008;Ruijs et al 2010;Lee et al 2012;Silva et al 2012).…”
Section: Patient-related Limitationsmentioning
confidence: 58%
“…Several studies show that patients with a family history of breast cancer are at higher risks in developing SPCs (ovary, oesophagus, stomach, leukaemia, non-Hodgkin's lymphoma) due to genetic susceptibility (Welcsh & King 2001;Prochazka et al 2006;Lynch et al 2008;Ruijs et al 2010;Lee et al 2012;Silva et al 2012). It is well documented in the literature that women with BRCA1 and BRCA2 genes are more susceptible to develop breast cancers than women lacking these genes.…”
Section: Patient-related Limitationsmentioning
confidence: 99%
“…A woman who is diagnosed with breast cancer before the age of 30 years and is not found to have a pathogenic BRCA mutation has an estimated 4-8% likelihood of having a TP53 mutation [3,[8][9]. Women with breast cancer diagnosed between ages 30 and 39 years may also have a small increased risk of having a TP53 mutation [10]. Gynecologists should refer patients with early pre-menopausal breast cancer for genetic testing for TP53 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A single study found one pathogenic variant out of 67 Pakistani BRCAx women (1.5%) with negative family history diagnosed before 30 years (Rashid et al, 2012). When it comes to BRCAx early onset breast cancer patients unselected for family history, TP53 carrier frequencies were estimated at 7.7% for women diagnosed before the age of 30 years (McCuaig et al, 2012), or between 2.3% and 4.2% for women of different ancestries diagnosed before 36 years (Ang, Lim, Yong, & Lee, 2009;Carraro et al, 2013;Lee et al, 2012;Tinat et al, 2009). Ginsburg et al, 2009, however, found no carriers out of only 52 BRCAx women of varying ancestries, all diagnosed with breast cancer before 30 years.…”
Section: Tp53-targeted Studies: Frequency Of Tp53 Carriers In Nonconvmentioning
confidence: 99%